2015
DOI: 10.1155/2015/876484
|View full text |Cite
|
Sign up to set email alerts
|

Antiamnesic Effect ofActinidia argutaExtract Intake in a Mouse Model of TMT-Induced Learning and Memory Dysfunction

Abstract: The antiamnesic effects of ethyl acetate fraction from Actinidia arguta (EFAA) on trimethyltin- (TMT-) induced memory impairment were investigated to find the possibility of functional food substances. EFAA showed a potent AChE inhibitory effect (IC50 = 53 μg/mL) and efficient neuroprotection against H2O2-induced oxidative stress. The administration of EFAA significantly decreased TMT-induced cognitive deficit in Y-maze, passive avoidance, and Morris water maze (MWM) tests. After the behavioral tests, the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…Studies have demonstrated that TMT exposure enhanced AChE staining in the hippocampal dentate gyrus, 23) and administration of TMT in mice resulted in a significant increase in AChE activity 24,25) ; such effects were observed in our study as well. We demonstrated that BP regulated the TMT-induced AChE overactivity in brain tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have demonstrated that TMT exposure enhanced AChE staining in the hippocampal dentate gyrus, 23) and administration of TMT in mice resulted in a significant increase in AChE activity 24,25) ; such effects were observed in our study as well. We demonstrated that BP regulated the TMT-induced AChE overactivity in brain tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, anti-amnestic activity has been reported from natural products such as pine needle extract [ 19 ], Avena sativa extract [ 20 ] and Actinidia argute extract [ 21 ]. The extract of Oldenlandia diffusa is reported to have anti-inflammatory [ 22 ] and anti-cancer activity in colorectal [ 23 ], liver [ 24 ] and breast cancers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…After that, the mouse was allowed to move freely for 8 min., and spontaneous spatial preference behavior was recorded by the Smart 3.0 video tracking system (Panlab, Barcelona, Spain). The percentage of spontaneous spatial preference behavior was calculated according to the following formula: (Number of alternations/(Total number of arm entries-2))×100 [19].…”
Section: Methodsmentioning
confidence: 99%
“…On the first day, the mouse was left in the bright space for 1 min., and when the gate was opened and the mouse completely passed into the dark side, the gate was closed and an electric shock (0.5 mA, 3 s) was applied on the foot. After the training trials, on the second day, the mouse was placed in the bright space and the step-through latency time that was taken to move to the dark space was measured (the step-through latency maximum testing time: 300 s) [19].…”
Section: Methodsmentioning
confidence: 99%